MANAGEMENT OF BUSINESS LEGALITY FOR MSMEE ENTERPRISES IN BATAM CITY THROUGH ONLINE SINGLE SUBMISSION WEBSITE SERVICE (MARIYUK.ID & PONDOK SEBLAK) - Ajizah Ajizah; Eko Nurisman (Universitas Internasional Batam, 2022)
Providing legal counseling and legal assistance regarding the importance of registering for business licensing for Micro, Small and Medium Enterprises (IUMK) in Batam City by using the OSS (Online Single Submission) system service in accordance with the provisions of Government Regulation no. 24 of 2018. Based on the results of research that found the author, it can be seen that there are obstacles in implementing the legality registration of UMKM business licensing using the OSS service system in Batam City, due to the lack of education and knowledge of UMKM business actors. This community service activity is carried out in the form of legal assistance and is given to both UMKM business owners in Batam City. and the owners of UMKMs Mariyuk.id and Pondok Seblak also provide opportunities for authors to provide legal assistance when registering for business permits. In this case, the owners of UMKM is also feel the benefits of having a business permit in order to get convenience in carrying out administration. The method used by the author is the method of advocacy and legal education. In this case, the UMKM business owners Mariyuk.id and Pondok Seblak also have awareness about the importance of registering the legality of business licensing